AROGYA Intelligent Health Care Application (Global Journal of Computer Science and Technology, 2021)
People of today pay less attention to their daily diet due to their busy lifestyles. Therefore, there is a great tendency to contract chronic non-communicable diseases. Furthermore, the lack of nutritious meals and daily exercise causes chronic non-communicable diseases in people with no age difference. In our first part, we developed to predict specialization in cardiology using symptoms. However, when we refer to a doctor, we must at least know what specialist should know based on their symptoms. In addition, there is a problem with the recipe. If the pharmacist has misread the prescription given by the doctor, patients can receive bad medications, leading to terrible side effects and even death due to careless writing by the doctor. As a solution, an application function can be proposed that will be developed in the project and the function should be able to improve the readability and intelligibility of the patient with prescription drugs. Therefore, the patient always knows the prescribed medications through the application to avoid the problem mentioned above. According to the 2016 pharmaceutical magazine, there are cholesterol and diabetic patients suffering mainly from chronic non-communicable diseases in Sri Lanka.